2021
DOI: 10.3389/fnins.2021.652715
|View full text |Cite
|
Sign up to set email alerts
|

Early-Stage Repetitive Transcranial Magnetic Stimulation Altered Posterior–Anterior Cerebrum Effective Connectivity in Methylazoxymethanol Acetate Rats

Abstract: The aim of the current resting-state functional magnetic resonance imaging (fMRI) study was to investigate the potential mechanism of schizophrenia through the posterior–anterior cerebrum imbalance in methylazoxymethanol acetate (MAM) rats and to evaluate the effectiveness of repetitive transcranial magnetic stimulation (rTMS) as an early-stage intervention. The rats were divided into four groups: the MAM-sham group, vehicle-sham group, MAM-rTMS group, and vehicle-rTMS group. The rTMS treatment was targeted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…In our quest to explore the subtle frontal‐posterior imbalance, our early experiment has suggested that central carbon metabolism disturbance and mitochondrial dysfunction may underlie the ReHo alterations 15 . Furthermore, in a prior fMRI study, we identified the nucleus accumbens as a central hub, transmitting rTMS effectiveness from posterior to frontal cortex 51 . Additionally, a separate structural MRI study hinted at the significance of hippocampus volume reversal in neuromodulation (under revision) 52 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our quest to explore the subtle frontal‐posterior imbalance, our early experiment has suggested that central carbon metabolism disturbance and mitochondrial dysfunction may underlie the ReHo alterations 15 . Furthermore, in a prior fMRI study, we identified the nucleus accumbens as a central hub, transmitting rTMS effectiveness from posterior to frontal cortex 51 . Additionally, a separate structural MRI study hinted at the significance of hippocampus volume reversal in neuromodulation (under revision) 52 .…”
Section: Discussionmentioning
confidence: 99%
“… 15 Furthermore, in a prior fMRI study, we identified the nucleus accumbens as a central hub, transmitting rTMS effectiveness from posterior to frontal cortex. 51 Additionally, a separate structural MRI study hinted at the significance of hippocampus volume reversal in neuromodulation (under revision). 52 Our previous research has already highlighted the potential of this objective neuroimaging biomarker in guiding neurotherapeutic approaches for MPDs.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased GABA may underlie neural mechanisms for increased ALFF in posterior regions in atypical depression [45]. Of note, both human and animal neuroimaging studies have observed excitatory effects of high-frequency rTMS and inhibitory effects of low-frequency rTMS on OCC [38, 46, 47]. Hence, in attempt to dampen the increases in posterior ALFF, we delivered low-frequency rTMS to the OCC in atypical depression.…”
Section: Discussionmentioning
confidence: 99%
“…Repetitive transcranial magnetic stimulation (rTMS) is a non-invasive neuromodulation technique that has been shown to induce short ("on-line") and long ("off-line") effects in different ways (2). The application of magnetic pulses to a target location in the brain repetitively generates long-lasting beneficial effects persisting for several weeks or even months after treatment (3)(4)(5)(6). rTMS has been approved by regulatory agencies as a therapeutic tool for a number of neuropsychiatric disorders, such as drug-resistant depression and obsessivecompulsive disorder (7,8).…”
Section: Introductionmentioning
confidence: 99%